Mortality and survival patterns of childhood lymphomas: geographic and age‐specific patterns in Southern‐Eastern European and SEER/US registration data. Issue 4 (19th September 2016) - Karalexi, Maria A.; Georgakis, Marios K.; Dessypris, Nick; Ryzhov, Anton; Zborovskaya, Anna; Dimitrova, Nadya; Zivkovic, Snezana; Eser, Sultan; Antunes, Luis; Sekerija, Mario; Zagar, Tina; Bastos, Joana; et al.
Abstract: Childhood (0‐14 years) lymphomas, nowadays, present a highly curable malignancy compared with other types of cancer. We used readily available cancer registration data to assess mortality and survival disparities among children residing in Southern‐Eastern European (SEE) countries and those in the United States. Average age‐standardized mortality rates and time trends of Hodgkin (HL) and non‐Hodgkin (NHL; including Burkitt [BL]) lymphomas in 14 SEE cancer registries (1990‐2014) and the Surveillance, Epidemiology, and End Results Program (SEER, United States; 1990‐2012) were calculated. Survival patterns in a total of 8918 cases distinguishing also BL were assessed through Kaplan‐Meier curves and multivariate Cox regression models. Variable, rather decreasing, mortality trends were noted among SEE. Rates were overall higher than that in SEER (1.02/10 6 ), which presented a sizeable (−4.8%, P = . 0001) annual change. Additionally, remarkable survival improvements were manifested in SEER (10 years: 96%, 86%, and 90% for HL, NHL, and BL, respectively), whereas diverse, still lower, rates were noted in SEE. Non‐HL was associated with a poorer outcome and an amphi‐directional age‐specific pattern; specifically, prognosis was inferior in children younger than 5 years than in those who are 10 to 14 years old from SEE (hazard ratio 1.58, 95% confidence interval 1.28‐1.96) and superior in children who are 5 to 9 years old from SEER/United States (hazard ratio 0.63, 95% confidence interval 0.46‐0.88) than in those who are 10 to 14 years old. In conclusion, higher SEE lymphoma mortality rates than those in SEER, but overall decreasing trends, were found. Despite significant survival gains among developed countries, there are still substantial geographic, disease subtype‐specific, and age‐specific outcome disparities pointing to persisting gaps in the implementation of new treatment modalities and indicating further research needs.